Injury to the Obturator Artery During Periacetabular Osteotomy: A Case Report. Issue 1 (January 2016) - Toki, Shunichi; Nagamachi, Akihiro; Yonezu, Hiroshi; Adachi, Keisuke; Inoue, Kazumasa; Naito, Masatoshi
Abstract : Case: We describe a middle-aged woman who had undergone periacetabular osteotomy (PAO) on both hips successively within a two-year period. Although the first PAO was successfully performed on the right hip without any complications, injury to the obturator artery occurred during the subsequent PAO on the left hip. In this case, the obturator artery seemed to be injured at the medial base of the iliopectineal eminence during osteotomy. Conclusion: PAO has been employed as a reconstructive surgery for acetabular dysplasia. However, given the proximity of intrapelvic vascular structures, there is a risk of iatrogenic vascular injury.